2018
DOI: 10.1158/1078-0432.ccr-17-1323
|View full text |Cite
|
Sign up to set email alerts
|

Higher Absolute Lymphocyte Counts Predict Lower Mortality from Early-Stage Triple-Negative Breast Cancer

Abstract: Tumor-infiltrating lymphocytes (TIL) in pretreatment biopsies are associated with improved survival in triple-negative breast cancer (TNBC). We investigated whether higher peripheral lymphocyte counts are associated with lower breast cancer-specific mortality (BCM) and overall mortality (OM) in TNBC. Data on treatments and diagnostic tests from electronic medical records of two health care systems were linked with demographic, clinical, pathologic, and mortality data from the California Cancer Registry. Multiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 45 publications
(41 reference statements)
3
54
2
Order By: Relevance
“…NLR is a routinely available marker of the systemic inflammatory response, and there is no significant difference of NLR value in distinct breast cancer subtype [16]. The presence of higher NLR in the blood has been recognized as a poor prognostic factor among triplenegative BC patients [10,11]. Meanwhile, a metaanalysis suggested that NLR was a good prognostic marker for HER2-positive BC and triple-negative BC, but not for luminal A and luminal B subtype BC [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NLR is a routinely available marker of the systemic inflammatory response, and there is no significant difference of NLR value in distinct breast cancer subtype [16]. The presence of higher NLR in the blood has been recognized as a poor prognostic factor among triplenegative BC patients [10,11]. Meanwhile, a metaanalysis suggested that NLR was a good prognostic marker for HER2-positive BC and triple-negative BC, but not for luminal A and luminal B subtype BC [17].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there are no authorized biomarkers reflecting systemic immune status [8]. Some studies indicated that low pretreatment neutrophil/lymphocyte ratio (NLR) was predictive factor of better DFS outcome in BC, especially in triplenegative BC patients [10][11][12]. In the HER2-positive subtype, few studies have explored the relationship between NLR and DFS of patients with or without trastuzumab treatment.…”
Section: Introductionmentioning
confidence: 99%
“…NLR is a routinely available marker of the systemic inflammatory response, and there is no significant difference of NLR value in distinct breast cancer subtype [16]. The presence of higher NLR in the blood has been recognized as a poor prognostic factor among triple-negative BC patients [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…NLR is a routinely available marker of the systemic inflammatory response, and there is no significant difference of NLR value in distinct breast cancer subtype [31]. The presence of higher NLR in the blood has been identified as a poor prognostic factor among triple negative BC patients [1,4].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there are no authorized biomarkers reflecting systemic immune status [18]. Some studies indicated that low pretreatment neutrophil/lymphocyte ratio (NLR) was predictive factor of better DFS outcome in BC, especially in triple-negative BC patients [1,4,13]. In the HER2-positive subtype, few studies have explored the relationship between NLR and DFS of patients with or without trastuzumab treatment.…”
Section: Introductionmentioning
confidence: 99%